Explaining different types of undeclared work: lessons from a 2019 Eurobarometer survey. Issue 6 (25th May 2021) - Williams, Colin; Oz-Yalaman, Gamze
Abstract : Purpose: Until now, most scholars have used one of four competing theories to explain undeclared work. Political economy theories explain undeclared work as resulting from the exclusion of workers from formal work and welfare, neo-liberal theories explain such work as a voluntarily chosen rational economic decision and neo-institutionalist and post-structuralist theories explain those engaging as social actors who disagree with the formal rules or seek to help others out respectively. Recognising that each theory focuses upon different employment relationships, this paper evaluates the proposition that these different theories are more explanations of different types of undeclared work. Design/methodology/approach: To evaluate this, data reported is collected in 2019 across 28 European countries (the 27 member states of the European Union and the United Kingdom) in special Eurobarometer survey 92.1 involving 27, 565 interviews. Findings: Of the 3.6% of citizens participating in undeclared work, 10% engage in undeclared waged employment, 42% in undeclared self-employment and 48% in undeclared paid favours. Reporting their rationales, 7% state purely political economy exclusion-driven reasons, 19% solely neo-liberal rational economic actor reasons, 20% purely social actor reasons and 54% mixed motives. A logistic regression analysis finds those engaging in undeclared waged employment significantly more likely to state purely exclusion-driven rationales, those engaging in undeclared self-employment significantly more likely to state neo-liberal rational economic actor and neo-institutionalist social actor rationales and those engaging in undeclared paid favours post-structuralist social actor motives. Practical implications: This finding suggests that the policy initiatives required to tackle undeclared work will vary according to the type of undeclared work addressed. These are outlined. Originality/value: Evidence is provided that a different weighting needs to be given to different theories when explaining each type of undeclared work.